The Arabidopsis thaliana Poly(ADP-Ribose) Polymerases 1 and 2 Modify DNA by ADP-Ribosylating Terminal Phosphate Residues - Taipakova, Sabira; Kuanbay, Aigerim; Saint-Pierre, Christine; Gasparutto, Didier; Baiken, Yeldar; Groisman, Regina; Ishchenko, Alexander A.; Saparbaev, Murat; Bissenbaev, Amangeldy K. (Frontiers in Cell and Developmental Biology, 2020)
Proteins from the poly(ADP-ribose) polymerase (PARP) family, such as PARP1 and PARP2, use NAD+ as a substrate to catalyze the synthesis of polymeric chains consisting of ADP-ribose units covalently attached to an acceptor molecule. PARP1 and PARP2 are viewed as DNA damage sensors that, upon binding to strand breaks, poly(ADP-ribosyl)ate themselves and nuclear acceptor proteins. The flowering plant Arabidopsis thaliana contains three genes encoding homologs of mammalian PARPs: atPARP1, atPARP2, and atPARP3. Both atPARP1 and atPARP2 contain poly(ADP-ribosyl)ating activity; however, it is unknown whether they could covalently modify DNA by ADP-ribosylating the strand break termini. Here, we report that similar to their mammalian counterparts, the plant atPARP1 and atPARP2 proteins ADP-ribosylate 5′-terminal phosphate residues in duplex DNA oligonucleotides and plasmid containing at least two closely spaced DNA strand breaks. AtPARP1 preferentially catalyzes covalent attachment of ADP-ribose units to the ends of recessed DNA duplexes containing 5′-phosphate, whereas atPARP2 preferentially ADP-ribosylates the nicked and gapped DNA duplexes containing the terminal 5′-phosphate. Similar to their mammalian counterparts, the plant PARP-catalyzed DNA ADP-ribosylation is particularly sensitive to the distance that separates two strand breaks in the same DNA molecule, 1.5 and 1 or 2 turns of helix for atPARP1 and atPARP2, respectively. PAR glycohydrolase (PARG) restored native DNA structure by hydrolyzing the PAR–DNA adducts generated by atPARPs. Biochemical and mass spectrometry analyses of the PAR–DNA adducts showed that atPARPs utilize phosphorylated DNA termini as an alternative to protein acceptor residues to catalyze PAR chain synthesis via phosphodiester bond formation between C1′ of ADP-ribose and a phosphate residue of the terminal nucleotide in DNA fragment. Taken together, these data establish the presence of a new type of DNA-modifying activity in Arabidopsis PARPs, suggesting a possible role of DNA ADP-ribosylation in DNA damage signaling and repair of terrestrial plants.